National Care System in Uruguay: Who benefits and who pays? - Verónica Amarante; Maira Colacce; Victoria Tenenbaum (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In this paper, we analyse two specific policies that make up the National Care System, a social policy being implemented in Uruguay. Through the calibration of a static tax benefit model, we estimate the distributive impact of the expansion of childcare services and home-based care for dependent elderly, both financed through a progressive direct tax on income. We discuss the importance of identifying who benefits from these services, and show that, in the Uruguayan case, the redistributive impact is very limited. Even if the benefits are significant for individual households, the overall impact is weak because the number of beneficiaries is small.
Keywords: D31; I38; J13; 330; childcare; elderly care; redistribution; microsimulation